A Study on Complaints and Grievances of Customers: With A Special Reference to Non Life Insurance Business in India (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Customers play a vital role in the growth and development of Insurance  Sector in developing countries like India. It is important for the insurance  providers to market themselves in a way that they attract new customers  as well as retain the old ones. For this, customer orientation or customer  centricity is the key. Customers’ satisfaction should be the foremost agen da for marketers so as to attract and retain the customers which would  also help them in remaining competitive in the current global arena. This  paper attempts to identify the major areas of customers’ grievances/ com plaints in non life insurance business in India and attempts to categorise  these complaints as a part of different Marketing Mix elements. This pa per further examines the role of Insurance Regulatory and Development  Authority of India and insurance companies in providing a solution to  resolve these complaints.
Keywords: Indian Insurance Sector; Customers’ Grievances; Insurance Regulatory and Development Authority of India; Marketing Mix